OpenWorkFlow—Development of an open-source synthesis-platform for safety investigations in the site selection process - Christoph Lehmann; Lars Bilke; Jörg Buchwald; Nico Graebling; Norbert Grunwald; Julian Heinze; Tobias Meisel; Renchao Lu; Dmitri Naumov; Karsten Rink; Ozan Özgür Sen; Philipp Selzer; et al. (Grundwasser, 2024)
The identification of appropriate locations for secure nuclear waste disposal, a crucial aspect of Germany’s nuclear phase-out strategy (StandAG 2017), remains a significant scientific, technical, and political challenge worldwide. The selection and safety assessment of sites demand extensive applications of numerical methods. The OpenWorkFlow project, initiated by Bundesgesellschaft für Endlagerung (BGE), develops a new, open synthesis platform to virtualise repository systems. The simulation platform will evaluate far-field and near-field processes, supporting the site selection process first and the geotechnical design of repository systems later on. The project’s development philosophy adheres to the principles of continuity and innovation. Through continuous scientific development, the OpenWorkFlow platform will remain at the forefront of science and technology. Furthermore, as a digital platform, OpenWorkFlow employs up-to-date IT methods and constantly evolving software concepts. As its name suggests, OpenWorkFlow (OWF) is an open platform, developed on the basis of FAIR principles as an open-source project, inviting community participation. This paper primarily focuses on the technical aspects of OWF, with only a brief discussion of conceptual principles and modelling methods. In the second part of the manuscript, demonstration examples from different scales are presented to illustrate the current technical status of OWF and to emphasize the requirement for further development.